On the Ellipsis: Singapore, Kafka and If We Dream Too Long - Fernando, Jeremy (SARE: Southeast Asian Review of English, 2017)
Up to 2010, the Singapore Tourist Board used the slogan Uniquely Singapore, as a part of its worldwide promotion of the city-state. One could deride it not so much for being bad (for what could be a matter of taste) as for being absurd- as absurd as the fact that the city is also branded as a "global city." Whilst there is nothing intrinsically problematic about situating oneself as global, it suggests that what is unique about Sinagpore is precisely the fact that it can be like any other ’global’ city in the world.